2008
DOI: 10.1051/mmnp:2008081
|View full text |Cite
|
Sign up to set email alerts
|

On the Relations Between 2D and 3D Fractal Dimensions: Theoretical Approach and Clinical Application in Bone Imaging

Abstract: Abstract. The inner knowledge of volumes from images is an ancient problem. This question becomes complicated when it concerns quantization, as the case of any measurement and in particular the calculation of fractal dimensions. Trabecular bone tissues have, like many natural elements, an architecture which shows a fractal aspect. Many studies have already been developed according to this approach. The question which arises however is to know to which extent it is possible to get an exact determination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Transforming a 2D projected image into a three‐dimensional (3D) structure is a mathematical challenge . However, several kinds of texture analysis methods, such as Fourier conversion, fractal analysis, and run‐length analysis, have been proposed as indirect measurements of 3D trabecular bone microarchitecture . These methods analyze trabecular structures according to different statistical properties of pixels in relation to density, computing a feature strongly related to the 3D parameters of the projected trabecular bone.…”
Section: Estimation Of 3d Indices From a 2d Projected Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Transforming a 2D projected image into a three‐dimensional (3D) structure is a mathematical challenge . However, several kinds of texture analysis methods, such as Fourier conversion, fractal analysis, and run‐length analysis, have been proposed as indirect measurements of 3D trabecular bone microarchitecture . These methods analyze trabecular structures according to different statistical properties of pixels in relation to density, computing a feature strongly related to the 3D parameters of the projected trabecular bone.…”
Section: Estimation Of 3d Indices From a 2d Projected Imagementioning
confidence: 99%
“…(41,42) However, several kinds of texture analysis methods, such as Fourier conversion, fractal analysis, and run-length analysis, have been proposed as indirect measurements of 3D trabecular bone microarchitecture. (41)(42)(43)(44)(45) These methods analyze trabecular structures according to different statistical properties of pixels in relation to density, computing a feature strongly related to the 3D parameters of the projected trabecular bone. These techniques provide a global estimate of bone quality, but they are not direct physical measurements of trabecular parameters.…”
Section: Estimation Of 3d Indices From a 2d Projected Imagementioning
confidence: 99%
“…Although there is a known relationship between d f,3D and d f,slice for the Hausdorff dimension, an alternative approach to describing fractal objects that is computationally challenging to calculate, there is no such established relationship for the Minkowski-Bouligand dimension (61,62). As such, one cannot immediately compare the fractal dimension obtained through 2D confocal imaging to those predicted from percolation theory.…”
Section: Comparison Of Structural Features To Critical Gelation Predictionsmentioning
confidence: 99%
“…Although equation 11predicts that the power-law exponent m of the size dependence of strength is inversely related to the exponent q of the mesh-length distribution, actual experimental verification is difficult since the q involved is for the mesh-length distribution in 3-D but the initial dislocation pattern can only be conveniently imaged in the transmission electron microscope (TEM) as 2-D projections. Even if the TEM tomography technique is used, the sampling is still from thin slices of the 3-D sample, and so is still based on 2-D. Zaiser et al (Zaiser et al, 1999) assumed that the fractal dimension of a 3-D dislocation network is that of its 2-D projection plus one, but more recent work has shown that there is no general relation between the dimensions of a 3-D fractal and its 2-D projections (Akkari et al, 2008). Here, in order to proceed, we take a simplification step by arguing that, instead of equation 7, the ensemble yielding rate ̇ can be estimated by sampling from a 2-D projection of the network.…”
Section: Sampling From 2-d Projections Of 3-d Dislocation Networkmentioning
confidence: 99%